Development of Geography Based Teaching Materials of Local Excellence - Sagaf, Safrudin; Tamalene, Muhammad Nasir; Ariyuni, Vrita Tri; Azhim, Muhamad Ihsan; Musyawarah, Rahma (UNM Geographic Journal, 2018)
1. The purpose of this research is to know: 1) Product of teaching material (module) of Basic Pedosphere geography in SMA Negeri 5 Ternate by using education based on local advantage 2). To know the feasibility of product of teaching materials (module) of geography at SMA Negeri 5 Kota Teranate. Data collection using intrument in the form of questionnaire,, questionnaire that used consist of two part that is part I in the form of assessment questionnaire and part II in the form of suggestion sheet and comment from validator. Data were analyzed by using qualitative descriptive analysis. The result of the research shows that (1) The compilation of geography-based teaching materials based on local advantage in the form of module to facilitate teaching and learning activities for teachers and students in SMA and MA Class X especially in SMA Negeri 5 Ternate. (2) used in high school and MA Class X especially in SMA Negeri 5 Ternate City..